Pengaruh Pendidikan Kewirausahaan dan Dukungan Keluarga terhadap Minat Berwirausaha Mahasiswa - Zaidatul Najiyyah; Heni Purwa Pamungkas (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The high unemployment rate, particularly among college graduates, is a serious problem facing Indonesia. This situation necessitates strategic efforts to develop the potential of the younger generation so that they are not merely job seekers but are able to create their own jobs through entrepreneurial activities. Students, as part of the younger generation, are expected to have a strong interest and motivation for entrepreneurship. This study aims to analyze the influence of entrepreneurship education and family support on the entrepreneurial interest of students in the Economics Education Study Program at Surabaya State University. This study uses a quantitative approach with an associative research type, which aims to determine the relationship and influence between variables. The study sample consisted of 197 students selected using a simple random sampling technique to ensure fair representation of the population. The research instrument was a questionnaire designed to measure students' perceptions regarding the entrepreneurship education they received and the extent to which family support influenced their decisions to become entrepreneurs. The collected data were analyzed using SPSS software to test the significance of the influence between variables. The analysis results indicate that both entrepreneurship education and family support have a positive and significant influence on students' entrepreneurial interest. These findings emphasize the importance of implementing applicable and inspiring entrepreneurship education, as well as the need for family involvement in providing moral and material support. Thus, the combination of formal education at university and family support can be a crucial factor in fostering an entrepreneurial spirit among students. This research recommends improving the quality of entrepreneurship curricula and family mentoring programs to support young entrepreneurs.